Impacts and issues of a social innovation approach to development finance: a case study of Zoona - Phiri, Lelemba Chitembo (Research of GSB, 2018)
This paper seeks to orientate research on the issues and impacts of pursuing a social innovation approach to development finance and the extent to which it impacts the development of economic, personal and social capital in developing countries. It draws on conceptual ideas around the evolution of development finance from a pure aid perspective to more innovative approaches that seek to increase uptake of development funds where they are needed most (at the base of the pyramid) and reduce fungibility. The paper provides an exploratory case study analysis of attempts by Zoona, a socially innovative private organization in Zambia that is leveraging mobile technology to increase access to finance and financial services to small and micro businesses and the unbanked in Zambia using an agent network. The research was qualitative study and gathered insights from 11 agents and 8 employees through 19 personal interviews. A hybrid approach to thematic analysis was employed in the research and results revealed that whilst Zoona's work was enabling economic and personal growth for the agents it was not necessarily building social capital within communities. The paper concludes with some recommendations on how the concept of socially innovative approaches to development finance, as supplementary forms of distributing development funds to traditional forms, can be improved on when applied by private organizations and local networks to enable the development of economic, personal and social capital and develop the capacity of communities.